ANALISIS PENGARUH CORPORATE TAX, LEVERAGE EFFECT, RISKY DEBT, MULTIACTIVITY FIRM DAN DEGREE OF OPERATING LEVERAGE TERHADAP SYSTEMATIC RISK PADA PERUSAHAAN NON-KEUANGAN KOMPAS100 TAHUN 2010-2015 - Lumbanradja, Ramos; Arfinto, Erman Denny (Diponegoro Journal of Management, 2016)
This Research  aimed  to analyze  the influence  of  Corporate  Tax,  Leverage  Effect,  Risky Debt, Multiactivity  Firm and   Degree Of Operating  Leverage  to Systematic  Risk. Case study on non-financial  company  in  KOMPAS100   during  the  period  2010-  2015.  By  using purposive sampling  method  obtained  a  sample  of  22  companies. Company  data  used  in  this  study  was obtained from the Indonesian Capital Market Directory for 2010-2015 and www.bloomberg.com. The analysis technique used is Ordinary Least Squares Regression (OLS). The results showed only a Corporate Tax which has positive and not significant against Systematic Risk.   Leverage Effect, Risky Debt and Multiactivity Firm which has positive and significant against Systematic Risk, while DOL does not affect the Market Value Added.